Student Team Achievement Division Learning Model and Student Process Skills - Kamid, Kamid; Winarni, Sri; Rohati, Rohati; Pratama, Wahyu Adi; Triani, Elza (Universitas Pendidikan Ganesha, 2022)
There are still many students who have difficulty learning mathematics. It is because students feel that learning mathematics is complicated. This problem has an impact on low student learning outcomes. One way to make it easier for students to learn is to use an appropriate learning model. This study aims to compare and correlate student response variables in the student team achievement division learning model of block and cube material and student process skills. This type of research is quantitative experimental research by comparing four classes using process skills variables and student responses to student team learning outcomes. The sampling technique used was purposive sampling with a sample size of 144 students from a population of two public elementary schools and two Islamic elementary schools. The technique used to collect data is a questionnaire. The instrument used to collect data is a questionnaire. The data analysis used was quantitative with the help of SPSS 25 statistics to find descriptive statistics, test assumptions, and test hypotheses. Based on the t-test, it is known that there are significant differences in students' process skills in each school and student responses to the Student team achievement division learning model on the volume of blocks and cubes in each school. Based on the correlation test, there is a relationship between students' process skills on student responses with the student learning model of team achievement division on the material of volume of blocks and cubes between schools.